Thickness dependence of the total magnetic moment per atom in the Cu/Ni/Cu/Si(001) system - Hope, S; Lee, J; Rosenbusch, P; Lauhoff, G; Bland, J; Ercole, A; Bucknall, D; Penfold, J; Lauter, H; Lauter, V; Cubitt, R (1997)
Systematic measurements of the magnetic moment per Ni atom in Cu/Ni/Cu/Si(001) structures have been made using polarized neutron reflection (PNR) for Ni thicknesses in the range 30Å<t<400å (mcxd),="" (moke),="" (rheed)="" 100="" 30="" <lz="" a="" above="" alternating="" and="" are="" at="" atom="" bulk="" by="" circular="" corroborated="" cu="" dichroism="" diffraction="" dramatic="" effect="" electron="" estimate="" find="" for="" gradient="" high-energy="" in="" kerr="" magnetic="" magneto-optical="" magnetometer="" measurements="" moment="" near="" ni-wedge="" of="" on="" order="" per="" polar="" reduction="" reflection="" results="" room="" same="" samples.="" si(001)="" structure="" studied="" t<100="" temperature.="" the="" these="" to="" using="" values="" variation="" was="" we="" with="" x-ray="" å="" å.="" å<t<150="">, <sz>, perpendicular anisotropy strength, and surface in-plane Ni lattice constant, respectively, during epitaxial growth. RHEED measurements show that the in-plane lattice constant falls by 1.7% in the Ni thickness range 30 Å<t<90 <lz="" for="" mcxd="" measurements="" reveal="" same="" the="" trend="" å.="">, <sz>, and total moment per atom versus Ni thickness as found for the total moment by PNR. Polar MOKE measurements confirmed the transition from a perpendicular easy axis towards an in-plane magnetic easy axis as has already been extensively studied in the literature. Comparison of the PNR results with RHEED measurements reveal a striking correlation between the increase of in-plane strain and reduction in magnetic moment per atom with decreasing Ni thickness. While a direct strain-induced variation of the moment based on bulk phase calculations cannot account for the magnitude of the moment variations we observe, we show that the results cannot be attributed to sample contamination, interdiffusion, or a reduction of the Curie temperature with decreasing Ni thickness. Furthermore, the presence of a magnetically dead layer in the samples is not consistent with the PNR results. The strong moment variation partially explains the large thickness range for which perpendicular anisotropy is observed in this system.</sz></t<90></sz></t<400å>